2017
DOI: 10.1016/j.esxm.2017.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Erectile Function Predicts Sexual Satisfaction in Men With Spinal Cord Injury

Abstract: IntroductionSpinal cord injury (SCI) is usually a sudden traumatic event and has a negative effect on sexual function.AimTo evaluate the characteristics of sexual activity in men with SCI and identify predictors of being sexually active and having a satisfactory sex life.MethodsWe assessed sexual activity profiles of men with SCI from a Brazilian tertiary rehabilitation center from February to August 2012. All patients older than 18 years with SCI for longer than 1 year were invited to participate. We analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 38 publications
0
16
0
2
Order By: Relevance
“…This study found that quality of sexual life significantly decreases after spinal cord injury and some of subjects were separated and divorce. In relate to this finding other researcher revealed that quality of sexual life depends on age of patient, duration of SCI, completeness of SCI, continence and having a partner were identified as an active sex life [13]. Community Level in Bangladesh…”
Section: Quality Of Sexual Life (Before and After Injury)mentioning
confidence: 80%
“…This study found that quality of sexual life significantly decreases after spinal cord injury and some of subjects were separated and divorce. In relate to this finding other researcher revealed that quality of sexual life depends on age of patient, duration of SCI, completeness of SCI, continence and having a partner were identified as an active sex life [13]. Community Level in Bangladesh…”
Section: Quality Of Sexual Life (Before and After Injury)mentioning
confidence: 80%
“…Pleasurable foreplay helps create a more intimate relationship [7,8,11,15,16,26]. Rigid erections allow men to be more sexually active and to engage in intercourse [27], and can also improve ejaculation frequency [4], intercourse satisfaction [7,12], and quality of life [28]. With appropriate pharmacological treatments, 84% of the men in this study were able to have reliable erections.…”
Section: Foreplay Intercourse and Desirementioning
confidence: 82%
“…Sexual satisfaction and quality of life have been shown to interact and reinforce one another [7,10,44,45]. The correlation between sexual satisfaction and intercourse satisfaction further indicates that restoring reliable erections is an important step in the sexual rehabilitation process [12,24].…”
Section: Sexual Satisfactionmentioning
confidence: 98%
See 2 more Smart Citations